Caries risk profiles in orthodontic patients: A 4-year follow-up study using the Cariogram model in governmental vs. private clinics - Naif A. Almosa; Ted Lundgren; Anas Al-Mulla; Dowen Birkhed; Heidrun Kjellberg (Elsevier, 2018)
Objectives: To (1) analyze caries-related factors and (2) evaluate caries risk using the Cariogram model for governmental and private orthodontic patients at de-bonding and 4 years after de-bonding. Materials and methods: Forty orthodontic patients with mean age of 26.4 years were recruited from a governmental (G) group (n = 20) and private (P) group (n = 20) and were examined at de-bonding (T1) and 4 years after de-bonding (T2). The examination included a questionnaire, plaque scoring, caries examination, bitewing radiographs, and assessment of salivary secretion rate, buffering capacity and cariogenic microorganisms. The data were entered into the Cariogram program to illustrate the caries risk profiles. Results: The chance to avoid new cavities was higher in P-group compared to G-group at T1 (58% and 31%, respectively) (P < 0.01) and T2 (77% and 52%, respectively) (P < 0.001). Plaque index was significantly higher in G-group, and fluoride was used significantly more in P-group at T1 and T2 (P < 0.05). The chance to avoid new cavities was higher at T2 compared to T1 (64% and 44%, respectively) (P < 0.001). Saliva secretion rate and buffer capacity were significantly increased, and the plaque index was significantly decreased at T2 compared to T1 (P < 0.01). Conclusion: According to the Cariogram, orthodontic patients were less likely to avoid new cavities at de-bonding and 4 years after de-bonding in government clinics compared to private clinics, and the caries risk significantly decreased 4 years after orthodontic treatment for all patients, regardless of the location of treatment. Keywords: Risk assessment, Cariogram, Orthodontics, Saudi Arabia